(untitled) (Research, Society and Development, 2021)
The objective of this study was to evaluate the influence of the packaging system on the useful life and post-harvest quality of lamb’s-ear leaves (Stachys byzantina L.). The sanitized sheets were packaged in four different packaging systems: (A) rigid polyethylene (PET), (B) PET together with ethylene-absorbing sachet, (C) PET wrapped with high barrier plastic film, and (D) PET together with an ethylene-absorbing sachet and wrapped with high barrier plastic film and stored at 7 ° C. Samples for physical-chemical analysis, bioactive compounds and antioxidant activity were removed before storing and at 5, 10 and 15 days of storage. The leaves contained in packages C showed less loss of mass and in system D they showed greater preservation of color attributes (L *, C * and °H). The packaging did not influence the contents of bioactive compounds, which showed higher values at 5 days of storage. The leaves stored in A, B, C and D showed high antioxidant capacity until the 15th day of storage. It was concluded that the quality atribof the lamb’s-ear leaves were kept in all packaging systems throughout 15 days of cold storage. The contents of bioactive compounds and antioxidant activity showed the highest values up to 5 days of storage at 7 ºC. Thus, considering the economic aspects and practicality in handling, packaging A is the most suitable for refrigerated storage (7 ºC) and commercialization of fresh lamb’s-ear leaves up to 15 days of storage.